EP-279 Impact of a Subspecialty Emergency Service on Emergency Laparotomy Workload. (9th August 2022) - Farrow, EZ; Cook, TA
Abstract: Aims: Subspecialist emergency surgical care, shared between Upper GI (UGI) and Colorectal (CR), can bring clinical benefits. Currently subspecialist emergency care is provided in around 20% of units but is likely to become more common in larger units with a view to driving improvement in outcomes. A subspecialty emergency service was introduced in our Trust in April 2020. The purpose of this study was to assess the impact of the subspecialty emergency service on emergency laparotomy workload for each team. Methods: Data recorded on the NELA Database over an 18-month period (April 2020 - September 2021) were reviewed. Consultant involvement and subspecialty team were recorded Results: There were 14 surgeons (7 UGI, 7CR) participating equally in the emergency service (two consultants available 24/7). There were 589 emergency laparotomies (mean 33/month) performed in the 18-month period, 6 were excluded from analysis due to incomplete data. A consultant surgeon was present for 94% of all cases. 357 cases (51 per surgeon) were performed under a CR consultant compared with 226 (32.3 per surgeon) under an UGI consultant. CR consultants performed more laparotomies out of hours then their UGI colleagues. Conclusions: There was good consultant involvement for all emergency laparotomies. CR surgeons performed 61.2% of emergency laparotomies reflecting the presenting pathology of emergency patients. This had an impact on the amount of out of hours operating for individuals within the service as a whole. These differences should be taken into consideration in units looking to establish a subspecialty emergency service.